Applications of Waste Cooking Oil Other Than Biodiesel: A Review - D. C. Panadare; V. K. Rathod* (Iranian Journal of Chemical Engineering)
Waste cooking oil (WCO) is being generated large scale all over the world; hence it has devised serious problems of its waste management. Organised collection of WCO in voluminous quantity is mainly used for the production of biodiesel. Most researchers focus primarily on the biodiesel generation from WCO, although other applications are also important and require attention. Objective of this review article is to highlight most of the aforementioned possible applications of WCO which may help in its utilization apart from biodiesel. It can be processed to obtain pyrolytic oil, hydrogen gas, biodiesel or electricity production by direct burning. Applications like combined heat and power generation (CHP) can utilize WCO with utmost efficiently. It can also be processed chemically to obtained biodegradable polyurethane sheets, greases, biolubricants, soaps and alkyd resins. Properly purified and sterilized WCO can be used as a carbon source in fermentation processes for the production of rhamnolipid biosurfactant and polyhydroxybutyrate (PHB). Waste cooking oil therefore can be considered as a potential waste which can be utilized as energy source and raw material for chemical or biological processes.